UJI LAMA PERENDAMAN DAN DOSIS PUPUK ORGANIK CAIR BIOLEMI TERHADAP PERTUMBUHAN VARIETAS INPARI 32 (Oryza sativa L.) DI PERSEMAIAN - Dyagung Prastio Yudistira; Widya Lestari; Badrul Ainy Dalimunthe (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
Until now, Indonesia's rice production has not been able to meet all the needs of the community. In the evaluation of seeds there are often seeds that are still abnormal and have not germinated. From the description above, the researcher is interested in examining